Editorial [Hot Topic: Recent Advances Into the Molecular Mechanisms and Therapeutic Targeting of Hepatocellular Carcinoma (Guest Editors: Dr. Mei-Sze Chua and Li Wang)] - Chua, Mei-Sze; Wang, Li (Anti-Cancer Agents in Medicinal Chemistry, 2011)
This special issue focuses on hepatocellular carcinoma (HCC), the predominant form of adult liver cancer, and also the third most common cause of cancer deaths worldwide. Despite well defined major etiologies and risk factors, and recent scientific advances in understanding hepatocarcinogenesis, survival of patients has not improved greatly over the past three decades. This is in part due to presentation and diagnosis of HCC at the advanced stages, when most potentially curative therapies such as resection, transplantation, or percutaneous and transarterial interventions are of limited efficacy. It is intrinsically resistant to conventional chemotherapy, and is rarely amenable to radiotherapy, leaving patients with no effective therapeutic options and a very poor prognosis. The development of more effective therapeutic agents and strategies is therefore much needed to improve the clinical management and prognosis of millions of HCC patients. HCCs are phenotypically and genetically heterogeneous tumors that commonly emerge on a background of cirrhosis (often caused by viral hepatitis or other chronic liver diseases). Recent insights into the biology of HCC suggest that certain signaling pathways and molecular alterations are likely to play essential roles in HCC development by promoting cell growth and survival. The malignant transformation of hepatocytes is a multistep process associated with preneoplastic changes in gene expression, resulting from altered methylation of genes, the actions of hepatitis B and C viruses, and point mutations or loss of heterozygosity. Improved knowledge in these critical areas has led to the identification of several potential therapeutic targets and has driven the development of molecularly targeted therapies. In this special issue, we first present an introduction to the basic molecular mechanisms underlying HCC development, including emerging areas of research such as small non-coding RNA molecules microRNAs and stem cells in liver cancer that hold great promise for future therapeutic applications, followed by reviewing several promising approaches and molecular targets for the treatment of HCC. Taken together, these molecular approaches offer novel and potentially more efficacious avenues to improve the clinical management and prognosis of HCC patients. The first article, “Molecular mechanisms of liver cancer”, by Dr. Wendong Huang's group, discussed important signaling molecules regulating hepatic inflammation and liver injury and their involvement in the development of liver cancer. The second article, “MicroRNA involvement in hepatocellular carcinoma”, by Dr. Massimo Negrini and his colleagues, provided a comprehensive overview of the role of small non-coding RNA microRNAs (miRNAs) in HCC. The article summarized the regulatory roles of miRNA on cell cycle, apoptosis, invasion and metastasis, and the β-catenin pathway, and also highlighted the value of using miRNA expression profile for HCC classification and prognostic stratification, and their blood circulating levels as HCC biomarkers. Lastly, the therapeutic potential of miRNA for HCC therapy was discussed. In the following article by Dr. Zhen Fan Yang's group, “Role of Stem cells in normal liver and cancer”, the authors introduced normal stem cells and putative cancer stem cells (CSCs) in the liver, and discussed signaling pathways, including the Bmil, Wnt/- βcatenin, Notch, PTEN, TGF-β, and sonic hedgehog pathways, that regulate pathophysiological activities of liver CSCs and the therapeutic potential by targeting CSCs in liver cancer. Nuclear receptors (NRs) are ligand-activated transcription factors regulating a wide variety of physiological and pathological functions in the liver, including hepatocarcinogenesis. The next article by Drs. Guodong Li and Grace Guo, entitled “Role of class II nuclear receptors in liver carcinogenesis”, summarized the roles of class II NRs, including PPARα, PPARβ/δ, PPARγ, RARs, FXR, CAR, PXR, LXRs, TRs, and VDR, in liver carcinogenesis and their potential application in the prevention and treatment of HCC. The poor prognosis of HCC patients is in part due to inaccurate diagnosis of HCC at an early stage. In the quest for more specific and sensitive HCC tumor markers, researchers have identified glypican-3 (GPC3) as being specifically over-expressed in HCC tumors but not in normal liver or other benign liver lesions. The article “Therapeutic potential of targeting glypican-3 in hepatocellular carcinoma” by Dr. Mark Allegretta provided the rationale for targeting GPC3 in HCC, and suggested strategies in which the functions of GPC3 can be inhibited to achieve therapeutic effects in HCC. As alluded to by Dr. Allegretta, the relationship between GPC3 and the Wnt pathway offers exciting opportunities to target these pathways in concert for more effective, broad-spectrum therapeutic intervention. In the contribution “Points of therapeutic intervention along the Wnt signaling pathway in hepatocellular carcinoma”, Dr. Miran Kim provided a comprehensive review of the many possibilities that various components of this pathway can be exploited for the treatment of HCC. Besides the critical Wnt signaling pathway, several other pathways are also major contributors towards cell proliferation, survival, metastasis, and angiogenesis in HCC development. These include the components of the receptor tyrosine kinase-activated pathways, such as the Raf, mitogen-activated protein extracellular kinase (MEK) and extracellular signal-regulated kinase (ERK) (Raf/MEK/ERK) pathway, the phosphatidylinositol 3-kinase (PI3K)/Akt/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway, the angiopoietins/Tie2 (Ang/Tie2) system, and the Janus kinase (Jak)-signal transducer/activator of transcription factor (Stat) (Jak/Stat) pathway. These pathways lie downstream of many important growth factors and their receptors that have been implicated in the development and progression of HCC. In his review entitled “Targeting receptor tyrosine kinase pathways in hepatocellular carcinoma”, Dr. Hung Huynh provided the latest pre-clinical and clinical developments on the efficacy of the emerging tyrosine kinase inhibitors, as well as the rationale for combination therapies for the treatment of advanced HCC. Next, an article by Dr. Jordi Muntané on “Targeting cell death and survival receptors in hepatocellular carcinoma” discussed the importance of death receptor (DR)-mediated cell signaling in HCC, and how the most important DRs in HCC (such as TNF-R1, CD95, and TRAIL-R1 and TRAIL-R2) can be targeted for enhanced therapeutic intervention. Lastly, HCC tumors have been reported to over-express the molecular target, ribonucleotide reductase M2 (RRM2), which is fundamentally involved in DNA synthesis. The function of RRM2 is dependent on iron, and can be competitively inhibited by gallium, which is chemically equivalent to iron. In his article “Hepatocellular carcinoma detection by gallium scan and subsequent treatment by gallium maltolate: Rationale and case study”, Dr. Lawrence Bernstein discussed the rationale for using an oral gallium compound, gallium maltolate, for the treatment of HCC, and presented a case study demonstrating the effectiveness of combining a 67Ga-scan with subsequent treatment of a patient's gallium-avid HCC. In conclusion, improved understanding of the molecular bases contributing to HCC, as well as the targets and strategies presented in this hot topic issue provide optimism for improved clinical management of HCC in the future, which will hopefully translate into prolonged patient survival for this typically fatal malignancy. The heterogeneous pathology of HCC, evidenced by the complex interplay of multiple essential pathways underlying HCC development, suggests that rational combination therapies will likely provide synergistic anti-tumor effects and better outcome.